Pharmaceutical Prices in the 21st Century - Babar, Zaheer-Ud-Din (Springer International Publishing : Imprint: Adis, 2015)
The book is an essential, comprehensive text onglobal drug pricing and covers a range of pharmaceutical pricing issues. It has twenty-two chapters in total;nineteenof which are case studieson an array of high, middle, and low income countries. The final three chaptersdiscussvalue-based pricing, innovation, prices and the pharmaceutical industry and the link betweenpharmaceutical policy and pricing. As the pharmaceutical market continues to expand, a number of pharmaceutical pricing strategies have been employed to control drug expenditures. The book explores this phenomenon further and willserve a valuable resource for policy makers, funders, social insurance institutions and drug companies.  About the author Zaheer-Ud-Din Babar, PhD is the Head of Pharmacy Practice at the School of Pharmacy, Faculty of Medical and Health Sciences, University of Auckland, New Zealand. A pharmacist by training and a PhD in pharmaceutical policy, Dr Babar is a recipient of the prestigious "Research Excellence Award" from the University of Auckland. His research program covers areas related to pharmaceutical policy and practice, encompassing access to and affordability of medicines, issues related to medicine pricing and pharmacoeconomics. Dr Babar has delivered invited lectures at Boston University School of Public Health, Harvard Medical School, the Austrian Health Institute and the Universities of Reading and Kingston. He has also acted as a consultant for the World Health Organization, Health Action International, the International Union against Tuberculosis and Lung Disease, the International Pharmaceutical Federation (FIP) and the Pharmaceutical Management Agency of New Zealand in the area of medicines pricing and policies. Dr Babar is the Editor in Chief of the Journal of Pharmaceutical Policy and Practice, www.joppp.org and can be reached at z.babar@auckland.ac.nz.